Fluid texts, moving arias, shifting sands; - Burden, M (2011)
Of course, many scholars working on opera and music theatre well understand the nature and origins of an opera libretto - or do they? The seductive lure of the printed page is strong, particularly when there is a score to ‘match’, or when there is no thematic catalogue to provide even a basic chart to navigate around the treacherous waters of the output of even some major 18th-century composers. A libretto is, after all, not ‘music’ - ‘that’s all very well, but why aren’t you talking about the music?’ - so why worry? Just hurry on to the matching score to identify the ‘composer’s intentions’, and all will be well. But will it? What does the printed page represent? The 18th-century London opera libretto was shaped and then manipulated to suit each revival, with the aria a moveable unit at the centre of this activity. So prevalent was this, that it has been argued that the resultant operas (pasticcios) remain ‘bugbears to an objective assessment of the nature and quality of Italian opera in eighteenth-century London’. But in one sense, the pasticcio - and the attendant issues of its method, interpretation, and performance - is representative of ‘the nature and quality’ of 18th-century London Italian opera, a fluid, vital, commercially driven, genre. This paper will not only revisit these issues, but will explore the notion that this method of opera compilation was only possible because of the popularity of one poet, Metastasio.